Soil Salinity and Water Status Effect on Growth of Seedlings of Zizyphus mauritiana (Rhamnaceae) - Ramoliya, P. J.; Pandey, A. N. (Indian Forester, 2007)
Effects of salinization of soil on emergence, growth and physiological attributes of seedlings of Zizyphus mauritiana Lam. (Rhamnaceae) were studied. A mixture of chlorides and sulphates of Na, K, Ca and Mg was added to the soil and salinity was maintained at 4.1, 5.2, 6.0, 7.1, 8.0 and 9.2 dSm-l. A negative relationship between percent seed germination and salt concentration was obtained. Seedlings did not emerge when soil salinity exceeded 8.0 dSm-1. Results suggested that this tree species is salt tolerant at seed germination stage. Seedlings survived and grew up to soil salinity 8.0 dSm-1 and eventually this species is salt tolerant at seedling stage too. Elongation of stem and root was retarded by increasing salt stress. However, this species has a tendency for rapid root extension and roots are able to extract water from very dry saline soil (7.6 % moisture). Leaves, stems, old roots and young roots were equally sensitive to salt stress. Reduction in growth of all tissues of seedlings was obtained with increasing soil salinity. Results also suggest that this tree species is a salt excluder. The ability of this plant to thrive in dry regions is further conferred by the xeromorphic features of its leaves.